Simplified 2D Finite Element Model for Calculation of the Bearing Capacity of Eccentrically Compressed Concrete-Filled Steel Tubular Columns - Anton Chepurnenko; Batyr Yazyev; Besarion Meskhi; Alexey Beskopylny; Kazbek Khashkhozhev; Viacheslav Chepurnenko (Applied Sciences, 2021)
Concrete-filled steel tubular (CFST) columns are widely used in construction due to effective resistance to compression and bending joint action. However, currently, there is no generally accepted effective calculation method considering both nonlinearities of the materials and lateral compression. The article proposes the finite element analysis method of concrete-filled steel tubular columns in a physically nonlinear formulation by reducing a three-dimensional problem to a two-dimensional one based on the hypothesis of plane sections. The equations of Geniev’s concrete theory of plasticity are used as relations establishing the relationship between stresses and strains. The technique was tested by comparing the solution with the calculation in a three-dimensional formulation in the LIRA-SAPR software package and with the experimental data of A.L. Krishan and A.I. Sagadatov. It has been established that the effective area of operation of circular-section columns are small eccentricities of the longitudinal force. The proposed approach can be applied to analyzing the stress–strain state and bearing capacity of pipe-concrete columns of arbitrary cross-sections. There are no restrictions on the composition of concrete, and the shell material can be steel and fiberglass.